2017
DOI: 10.1002/advs.201600480
|View full text |Cite
|
Sign up to set email alerts
|

Draw‐Spinning of Kilometer‐Long and Highly Stretchable Polymer Submicrometer Fibers

Abstract: A new method is developed to directly spinning perfectly uniaxial fibers in an ultrafast manner. Besides, this method can tune the fibers' diameter through adjusting processing parameters such as the feeding rate of precursors. Uniaxial nylon 66 fibers prepared via this method show superior mechanical properties due to the alignment in each level of the structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Comparable findings were noted in fibers composed of flexible polymers, where drawing and subsequent post-draw stretching resulted in improved mechanical properties, such as increased tenacity, attributed to enhanced strain alignment. 46 Here, Zhu et al 168 reported enhanced strength of wool keratin fibers through the introduction of dithiol chain re-bonding. The wet-spinning process was meticulously fine-tuned, including parameters like coagulation, oxidation, and posttreatment, to ensure the consistent production of regenerated keratin fibers with superior strength.…”
Section: Reeling Speed and Crystallinitymentioning
confidence: 94%
See 1 more Smart Citation
“…Comparable findings were noted in fibers composed of flexible polymers, where drawing and subsequent post-draw stretching resulted in improved mechanical properties, such as increased tenacity, attributed to enhanced strain alignment. 46 Here, Zhu et al 168 reported enhanced strength of wool keratin fibers through the introduction of dithiol chain re-bonding. The wet-spinning process was meticulously fine-tuned, including parameters like coagulation, oxidation, and posttreatment, to ensure the consistent production of regenerated keratin fibers with superior strength.…”
Section: Reeling Speed and Crystallinitymentioning
confidence: 94%
“…162,163 An approach that could potentially enhance the fiber tensile strength as well as toughness is to reduce their diameter to a level more closely resembling that of native dragline-silk, as this appears to influence the fibers' mechanical properties. 46 Here, Xiao et al 164 reported robust and resilient hierarchical shell-core fibers that emulate native spider silks, these fibers feature the shell's RSFs and CNFs. Fibers with a shell-core structure of RSF/CNF, characterized by meticulously monitored morphology, are constantly produced through wet-spinning employing a coaxial microfluidic apparatus.…”
Section: Post-stretching and Diametermentioning
confidence: 95%
“…[1] These benefits enable polymer microfibers to have an excellent potential in many applications such as biomedicine, [2][3][4][5][6] fiber optics, [7] sensors, [8,9] and water treatment. [10,11] Different approaches have been employed to produce micro-and nanofibers such as melt spinning, [12] wet spinning, [13] draw spinning, [14] macromolecular assembly, [15] and electrospinning, [16] techniques relying on the physical mechanism of solidification to produce fibers, i.e. the starting raw material is a polymer solution.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, fibers have undergone a revolution of thinning. A large number of synthetic and fabrication methods are still being researched for ultrathin fibers. Among these methods, blowspinning is an emerging method . Unlike other methods, it utilizes a high-speed airflow to stretch the polymer solution along the airflow direction (Figure a) .…”
Section: Introductionmentioning
confidence: 99%